Characteristics of specific reading disability in children from a neuropsychological clinic in Mexico City - Poblano Adrián; Borja Sonia; Elías Yolanda; García-Pedroza Felipe; Arias Ma de Lourdes (Instituto Nacional de Salud Pública, 2002)
Objective. This report describes the main clinical features associated with specific reading disability (RD) in a group of 778 school-age children studied in a Neuropsychological Clinic in Mexico City. Material and Methods. The study was performed retrospectively, using data abstracted from clinical records of subjects seen in 1995-1996. Children were mainly from low and middle economic strata and aged between 6 to 12 years. The following data were collected: age, gender, diagnosis, school grade, food intake, maternal complications during pregnancy, perinatal and postnatal neurological risk factors, and neurological signs and handedness. Results. Subjects with RD had a mean age of 102.9 months, were predominantly male (male female ratio, 2:1). Among the study group, 49.1% of the children were diagnosed with RD of a visuo-sensory-motor type, and 75.1% were from early school years (1st to 3rd grades); 27.6% showed evidence of malnutrition. A previous history of language disorders (49.2%), and a high frequency of perinatal risk factors and neurological soft signs were also found. Conclusions. This study shows that variables such as gender, food intake, and genetic and neurological risk factors, were associated with reading disabilities in school children.